Influence of the Soil Amрlification on the Seismic Response of Base Isolated Structures - ATIED, HAMDULLAH (İstanbul Kültür Üniversitesi, 2022)
This study investigates the influence of soil amplification due to local site conditions on the seismic response of a base-isolated structure. Soil amplification effects were evaluated using linear one-dimensional site response analysis with DEEPSOIL. The structural model used in this investigation is a shear frame on lead core rubber bearings. The force-displacement relationship of the lead core rubber bearings was modeled with the Bouc-Wen model. The dynamic analysis of the structural model was conducted using a MATLAB script. The seismic response of the base-isolated structural model was investigated using time history analysis with six earthquake-strong ground motion records. A comparison of the dynamic response of the structure directly subjected to the selected earthquake ground motions and the free surface ground motions obtained from site response analysis shows that local site conditions can significantly change the dynamic response of structures.
Toprak genişletmesinin taban izoleli yapıların sismik tepkisi üzerine etkisi
▪ Yüksek lisans tezi.
Keywords: MATLAB; DEEPSOIL; Soil Amplification; Seismic Isolation